ICD implantation and device therapy: Fabry vs hypertrophic cardiomyopathy. (25th November 2020) - Vijapurapu, R; Zegard, A; Leyva, F; Bradlow, W; Jovanovic, A; Hughes, D; Geberhiwot, T; Steeds, R.P
Abstract: Background: Cardiac involvement of Fabry disease (FD) includes left ventricular hypertrophy (LVH), inflammation, arrhythmia and sudden death. There are limited data regarding potential risk predictors and no definitive criteria exist to guide implantation of cardiac devices for primary prevention. Despite phenotypic similarities between FD and hypertrophic cardiomyopathy (HCM), FD is specifically excluded from the ESC sudden cardiac death risk prediction tool used for HCM. Purpose: To evaluate differences in device implantation and arrhythmic burden between advanced Fabry cardiomyopathy and HCM. Methods: This multi-centre, retrospective study including genetically confirmed FD and age/gender-matched HCM patients all of whom had an implantable cardioverter defibrillator (ICD). Data was collected prior to device implantation on disease characteristics, biomarkers and CMR imaging. Arrhythmia burden and changes in therapy were captured following implantation. Results: Of the UK FD population under follow-up, 50/880 had an ICD implanted (80% males, 51% non-classical mutation, mean age at device implantation 57±12 years). A comparator group included 64 age- and gender-matched HCM patients (67% males, mean age at implant 46±39 years). Baseline LV mass was greater in FD (291±97g/m 2 vs 218±78g/m 2, p=0.012). FD patients had higher troponin (95 vs 19ng/l, p<0.001) but similar NT-pro-BNP (1687 vs 888ng/l, p=0.086) levels. Indications for ICD insertion in FD included: presumed HCM dual pathology 14%, symptomatic NSVT 18%, asymptomatic NSVT 24%, co-existing long QT 2%, CRT-D 14%, no clear indication (primary prevention in the presence of multiple potential arrhythmic risk factors) 28%. All HCM patients were risk stratified and underwent device implantation based on an estimated 5-year SCD risk >4%. All FD patients had a SCD risk >4% using this risk calculator. Arrhythmia were more common in FD over shorter follow-up (37/50, 74% over 4.3±3.0 years vs 28/64 in HCM, 44% over 6.5±2.9 years, p=0.001). Notably, VT requiring anti-tachycardia pacing (ATP) +/− defibrillation therapy from the ICD was more frequent (FD: 14/50, 28% vs HCM: 8/64, 12%, p=0.055), as was immediate shock therapy for sustained VT (p=0.009, figure panel B). FD patients with arrhythmia were often older, had greater LV mass, a larger left atrium and a broader QRS duration. These clinical features tended to occur more frequently in FD than in the HCM group. Conclusion: This study has shown that delivery of device therapy in Fabry cardiomyopathy is higher than in HCM. Despite similar rates of asymptomatic NSVT, a higher rate of ventricular arrhythmia requiring ATP/defibrillation therapy occurred in FD. Although both FD and HCM had similar risk percentages according to the ESC calculator, active troponitis in FD was double that of HCM. Funding Acknowledgement: Type of funding source: None